The South African Cardiovascular Magnetic Resonance (SA-CMR) Registry: An Interim Analysis of Clinical Utility, Indications and Baseline Characteristics of Patients Undergoing CMR in a Single Centre in South Africa - Coccia,Cecilia Beatrice Irene (Department of Medicine, 2022)
Background Cardiovascular magnetic resonance (CMR) is a clinically useful imaging modality that is fast becoming a routine tool in clinical practice. In 2013, the results of the first multi-national registry, EuroCMR, were published. The study highlighted the clinical significance and impact of CMR in Europe. More recently, the global CMR registry (GCMR) has been established to standardise data from international centres in order to support the role of CMR across diverse patient demographics. Despite South Africa joining the GCMR network, the role of CMR in the South African context remains undefined and at present there is limited research pertaining to its use. The South African CMR (SA-CMR) registry was founded in 2016 with a view to gain insight into CMR in the South African setting. This interim analysis of the first 1,142 patients aims to establish the clinical use and indications for CMR, to assess the quality of CMR images and to the assess the baseline demographic and clinical characteristics of the cohort. Secondary objectives aim to ascertain the impact of CMR on patient management. Methods SA-CMR was designed to be a national registry that consists of both retrospective and prospective CMR data. This analysis reports on the single-centre experience at Groote Schuur Hospital, Cape Town. The retrospective arm consists of patients that underwent CMR at Groote Schuur Hospital (GSH) from its introduction in 2005 to April 2017. This interim analysis will assess the first 1,142 patients in this retrospective arm. Results Of the indications for use of CMR in Cape Town, the ascertainment of the presence of cardiomyopathies or their delineation accounted for 54% of scans performed. 15% were utilised to define congenital cardiac anomalies. The average age of patients undergoing CMR was 40 years old and there was a slightly increased percentage of female to male patients (52.65% vs 47.32%). Image quality was diagnostic in 99% of cases and adverse reactions from gadolinium contrast agent use only occurred in 0.18% of patients – of which none were fatal. 34% of scans showed either an alternative diagnosis or additive information which subsequently resulted in an alteration in clinical management of the patient. Conclusion In comparison with the European cohort, where the most important indication for CMR was risk stratification in suspected coronary artery disease, SA-CMR showed that, in the South African setting, CMR was utilised predominantly for investigation of cardiomyopathies. SACMR further supported CMR as a safe imaging technique which has assisted in diagnostics and clinical management of patients with cardiovascular disease in South Africa.